Potential use of electrochemically synthesized silver nanoparticles on rice panicle blight pathogen, Burkholderia glumae - Chaves-Bedoya, Giovanni; Padilla, Hilda Angélica; Ortiz-Rojas, Luz Yineth; Peña-Rodríguez, Gabriel (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Burkholderia glumae, is the main causal agent of bacterial panicle blight (BPB) in rice (Oriza sativa), a disease that generates production losses worldwide. Despite its economic importance, effective control measures and rice varieties with complete resistance to this disease have not yet been available. In this study, the antimicrobial activity of electrochemically synthesized silver nanoparticles (AgNPs) against B. glumae was evaluated. The AgNPs were synthesized with a DC power supply (UNI-T®) regulated at 24 V, which was connected to two cylindrical electrodes of high purity silver (Aldrich-99.99%) using distilled water as an electrolyte. The AgNPs concentration was determined by measuring the total dissolved solids (TDS) with a HandyLab 680 FK multiparameter. The antibacterial activity of these nanoparticles against B. glumae was determined by the broth macrodilution method at different concentrations (1-10 mg L-1). The minimum inhibitory concentration (MIC) was determined in 5 mg L-1 of AgNPs. The results revealed that AgNPs are a promising nanopesticide for controlling the BPB disease in rice.